Mechanical properties of 3D printed concrete with coarse aggregates and polypropylene fiber in the air and underwater environment. (16th May 2023) - Seo, Eun-A; Kim, Won-Woo; Kim, Sung-Wook; Kwon, Hong-Kyu; Lee, Ho-Jae
Highlights: 3D concrete printing was performed using coarse aggregates. Air and underwater environments for concrete preparation were compared. Both normal weight concrete and fiber-reinforced concrete were investigated. Mold casting and printing concrete preparation methods were compared. Existing models were evaluated for predicting the elastic modulus of all specimens. Abstract: In this study, three-dimensional concrete printing (3DCP) was performed for concrete with coarse aggregates in air and underwater environments for a comparative evaluation of the mechanical properties of the obtained samples. The base concrete mix was selected based on normal weight concrete (NWC) with ordinary Portland cement (OPC) as a binder, and the mechanical properties of the printed concrete applied using 3DCP and mold cast concrete were compared for analysis. For printability, fiber-reinforced concrete (FRC) with polypropylene fiber was additionally considered as a variable, and the fabrication method (printing and mold casting) and conditions (air and underwater environments) were varied. For the specimens fabricated using different materials, fabricating methods, and fabricating environments, the apparent density, compressive strength, splitting tensile strength, and stress–strain curves were comparatively analyzed. Considering the static elastic modulus calculated from the stress–strain curve, the correlation between the values obtained using design codes and those obtained via elastic modulus prediction models presented in previous studies was comparatively analyzed. When the concrete fabricated using the mold casting method was compared with the printed specimen, the density of the mold cast concrete was higher by 34 kg/m 3 compared to that of the printed specimen, and the specimen fabricated in the air showed a density that was 45 kg/m 3 greater compared to that of the specimen fabricated underwater. The compressive strength (28 days) was found to be approximately 8% higher in NWC compared to that in FRC, and the compressive strength of the underwater specimen was about 72% of that of the air specimen.